2006
DOI: 10.1007/s00381-006-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the success and failure of endoscopic third ventriculostomy in infants less than 1 year of age

Abstract: ETV should be considered as initial treatment and carries low morbidity in these infants. As the immune system rapidly matures, postponing shunt implantation for several months or even weeks would make an ETV procedure worthwhile. On the other hand, as success probability rapidly increases 4 months after birth, re-ETV should always be considered first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…1,2,4,6,7,9,11,16,18,20 Recently, we used confounder-adjustment techniques (propensity score modeling) to compare the failure rate of ETV versus shunt placement. 13 We found that, once adjusted for confounders, ETV is associated with a higher initial failure rate, but, over time, the failure rate becomes lower than that associated with shunt placement.…”
mentioning
confidence: 99%
“…1,2,4,6,7,9,11,16,18,20 Recently, we used confounder-adjustment techniques (propensity score modeling) to compare the failure rate of ETV versus shunt placement. 13 We found that, once adjusted for confounders, ETV is associated with a higher initial failure rate, but, over time, the failure rate becomes lower than that associated with shunt placement.…”
mentioning
confidence: 99%
“…Data from the literature suggest that the clinical response to ETV in adult patients with obstructive hydrocephalus is different from that in children, and the differences are secondary to the age at onset of hydrocephalus, CSF dynamics, and changes in brain viscoelastic properties 8,11,22) . Rates of success reported for ETV in patients 2 years old and younger vary from 0 to 83.3% with a mean of 47.8%, which is significantly lower than the success rate in older children 2,3,6,9,10,[12][13][14]16,[18][19][20][21]24,28,29) . However, when evaluating success rates of secondary ETV, Marton et al 22) reported that age does not have a statistically significant effect, which is also reflected by our data.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the authors noted that a second ETV should always be considered before shunt placement in young patients with a failed ETV, as the probability of ETV success rapidly increases 4 months after birth. 53 The largest study of ETV success in very young children was conducted in Uganda and it involved 153 children younger than 1 year. 54 The ETV success rate among these patients was 53%.…”
Section: Discussionmentioning
confidence: 99%